Kisah Amalan dan Karomah Abah Guru Sekumpul - M. Kautsar Thariq Syah (PT Inovasi Penelitian Terpadu, 2026)
This study examines his Sufi practices, karomah, and example as a guardian of God in Indonesia, particularly in South Kalimantan. The study employed library research, collecting data from various sources, books, journals, and historical records, then analyzing them through historical and Sufi approaches to interpret his role and influence. The results show that Abah Guru Sekumpul was a gentle, patient, compassionate, generous, and diligent scholar. Since childhood, he had developed spiritual abilities, including vision and the gift of seeing the unseen, which further developed through intensive education at Islamic boarding schools and under the guidance of expert teachers from Kalimantan to Mecca. His practices included religious teachings, maintaining prayer gatherings, and consistent practice of Sufism, which not only shaped his personality but also inspired thousands of worshippers. The charisma that accompanied his life—such as the ability to be present in several places simultaneously and extraordinary spiritual experiences—were manifestations of his closeness to God, not his primary goal, but rather the fruit of sincerity, discipline, and appreciation of the sharia, tarekat, and haqiqah. Furthermore, this study emphasizes the universal dimension of compassion in his Sufism, where compassion and respect embrace all groups, including those of different faiths. Abah Guru Sekumpul's sainthood continues to live on after his death through regular memorial services, spiritual influence, and the inheritance of prophetic teachings. The overall findings confirm that Abah Guru Sekumpul was a Sufi figure capable of integrating religious practice, morality, and social service, thus becoming a spiritual and social role model who continues to influence the people of Kalimantan and the Indonesian archipelago at large.